Coastal wetland management in the Great Barrier Reef: Farmer perceptions. (29th July 2021) - Oza, Tanvi Mihir; Lane, Ruth; Adame, Maria Fernanda; Reef, Ruth
Abstract: Poor water quality caused by intensive sugarcane farming has been among the main causes of coastal degradation around the Great Barrier Reef (GBR). Despite regulations and incentives, water quality in the GBR has yet to reach government targets, and there is an urgent need to investigate alternative management approaches. In this study, we have employed a social‐ecological approach to understand farmers' attitudes to existing nutrient and sediment management approaches, assess farmers' perceptions of managing coastal wetlands to ameliorate agricultural run‐off, and propose how these findings could inform integrative policy development for the GBR. We conducted semi‐structured interviews with sugarcane farmers in the Wet Tropics to understand perceptions of ecosystem services, coastal wetlands and industry challenges. We linked our analysis of key issues of concern to farmers with broader environmental and land use issues and have outlined future policy considerations in the face of socio‐economic and climatic change. Our conclusions emphasise the need to rethink future land tenure in low‐lying areas of North Queensland, the importance of considering ecosystem services provided by coastal wetlands in policy models and the need for a payments for ecosystem services (PES) model to safeguard the future of the GBR. Abstract : Around Australia's Great Barrier Reef, land tenure will need to be reconsidered in low‐lying areas of Queensland because of sea‐level rise and climate change. However, policy initiatives currently fail to consider social‐ecological relationships between agriculture and coastal wetlands, even though farmers are open to reserving low‐lying paddocks for coastal wetlands. Payments for ecosystem services may be an effective land use transition strategy for vulnerable farming communities situated in the critical coastal zone.